A Semiotic Analysis of Traditional Carvings in Traditional Houses of Orahili Sibohou Village, Gomo, South Nias - Afore Harefa; Clara Harefa; Maria Halawa; Anjelina Ndruru (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to uncover the semiotic meanings of traditional carvings in Nias traditional houses (Omo Hada) in Orahili Sibohou Village, Gomo, and to compare the visual and social characteristics between noble houses (Balugu/Si’ulu) and commoner houses (Banua Sato). The research employs a descriptive qualitative method with a semiotic approach. Primary data were gathered through direct observation of a ±500-year-old traditional house and in-depth interviews with the customary leader and heir of the Balugu house, Mr. Tandröziduhu Telaumbanua (A. Uco). The study is further supported by a literature review of